Hardiness and Optimism: Their Association with Work Readiness in Vocational High School Students - Risha Jovita; Pratista Arya Satwika (Green Publisher, 2025)
Vocational education, especially at the Vocational High School (SMK) level, plays an important role in preparing young workers who are ready to face the challenges of the world of work. Despite this, SMK graduates have been contributing to Indonesia's Open Unemployment Rate in recent years. One of the contributing factors is students' inadequate work readiness. Previous research found that internal factors have the greatest contribution to work readiness. Hardiness and optimism are two of the internal factors that are still limitedly studied in work readiness. This study aims to determine the relationship between hardiness and optimism in job readiness in vocational students. This study used quantitative methodology, with a research sample of 69 students in class XI at a vocational school in Surakarta obtained through a simple random sampling technique. The measuring instruments used are the Work Readiness Scale (?=0.944), Hardiness Scale (?=0.891), and Life Orientation Test-Revised (?=0,760). The multiple regression analysis results showed a significant relationship between hardiness and optimism in job readiness in vocational students. Hardiness and optimism together contribute an influence on work readiness of 59.7%. When tested partially, only hardiness showed a significant relationship with work readiness, while optimism did not. Educational institutions are advised to increase students' hardiness and optimism to be ready to enter the world of work.